Study on Optimization of Grouting Curtain Design of Damsin Karst Areas Based on Response Surface Methodology - XIE Mengshan; CAO Lei; GUO Xiaojing; LIU Xu; ZHANG Cong; JIANG Maiyong; LI Jinyou (Renmin Zhujiang)
Curtain grouting is an effective measure to solve the seepage problem of dams in karst areas.In order to optimize the grouting curtain design of dams in karst areas and effectively control the seepage flow and pressure of the dam foundation,a curtain service model of dams in karst areas is firstly built by using multi-field coupling software,and the evaluation standard of curtain service performance of dams in karst areas is put forward.Secondly,based on experimental design of Box-Behnken response surface,a regression model among curtain permeability coefficient,curtain height,curtain width,and Ca(OH)2 dissolution rate in the curtain body in karst areas is established.Finally,according to the fmincon function in Matlab,a model for optimizing design parameters of grouting curtain in karst areas is established,and the optimal combination of design parameters of curtain of a dangerous dam in the karst area is solved by taking the minimum curtain grouting amount as the optimization principle under the condition of satisfying the curtain service performance.The results show that the curtain permeability coefficient is the most important factor affecting the Ca(OH)2 dissolution rate in the dam curtain in karst areas,followed by the curtain height and width.In view of the safety and economic requirements of the project,it is suggested that the curtain height of 15.80 m and the curtain width of 4.51 m should be adopted in the curtain design of the dam in the karst area.The research results can provide a reference for evaluating the service performance of dam curtain in karst areas and offer a new idea for optimizing the design of grouting curtain of dams in karst areas.